Looking into cognitive impairment in primary‐progressive multiple sclerosis. (6th December 2017) - Petracca, M.; Sumowski, J.; Fabian, M.; Miller, A.; Lublin, F.; Inglese, M.
Abstract : Background and purpose: Cognitive impairment in primary‐progressive multiple sclerosis (PP‐MS) is correlated with global brain atrophy. Unfortunately, brain volume computation requires processing resources that are not widely available in clinical practice. Therefore, we decided to test the predictive role of retinal atrophy metrics on cognitive decline, applying them as a proxy of gray matter atrophy in PP‐MS. Methods: Twenty‐five patients with PP‐MS completed the Brief International Cognitive Assessment for Multiple Sclerosis and underwent spectral‐domain optical coherence tomography (OCT) and 3.0‐T magnetic resonance imaging. We tested, through a stepwise logistic regression, whether OCT metrics [retinal nerve fiber layer, ganglion cell + inner plexiform layer (GCIPL) and total macular volume] predicted cognitive impairment and explored the role of gray matter atrophy in mediating these correlations. Results: Among OCT metrics, only GCIPL was associated with cognitive impairment ( r p = 0.448, P = 0.036) and predictive of objective cognitive impairment (Wald [1] = 4.40, P = 0.036). Controlling for demographics, normalized brain volume and thalamic volume were correlated with GCIPL ( r p = 0.427, P = 0.047 and r p = 0.674, P = 0.001, respectively) and cognitive scores ( r p = 0.593, P = 0.004 and r p = 0.501, P = 0.017, respectively), with thalamic volume nearly mediating the association between GCIPL and cognition (Sobel z = 1.86, P = 0.063). Conclusions: The GCIPL thickness is a suitable measure of neurodegeneration. In comparison with brain atrophy, GCIPL offers higher histopathological specificity, being a pure correlate of neuronal loss, and may be a non‐invasive, easy‐to‐perform way to quantitatively evaluate and monitor neuronal loss related to cognitive impairment in PP‐MS.